R&D on a high-performance electromagnetic calorimeter based on oriented crystalline scintillators - Soldani M.; Argiolas N.; Bandiera L.; Baryshevsky V.; Bomben L.; Brizzolari C.; Canale N.; Carsi S.; Cutini S.; Davì F.; De Salvador D.; Gianoli A.; et al. (EPJ Web of Conferences)
Although inorganic scintillators are widely used in the design of electromagnetic calorimeters for high-energy physics and astrophysics, their crystalline nature and, hence, their lattice orientation are generally neglected in the detector design. However, in general, the features of the electromagnetic field experienced by the particles impinging on a crystal at a small angle with respect to a lattice axis affect their interaction mechanisms. In particular, in case of electrons/photons of (10 GeV) or higher impinging on a high-Z crystal at an angle of ≲ 1 mrad, the so-called strong field regime is attained: the bremsstrahlung and pair production cross sections are enhanced with respect to the case of amorphous or randomly oriented materials. Overall, the increase of these processes leads to an acceleration of the electromagnetic shower development. These effects are thoroughly investigated by the OREO (ORiEnted calOrimeter) team, and pave the way to the development of innovative calorimeters with a higher energy resolution, a higher efficiency in photon detection and an improved particle identification capabilities due to the relative boost of the electromagnetic interactions with respect to the hadronic ones. Moreover, a detector with the same resolution as the current state of the art and reduced thickness could be developed. An overview of the lattice effects at the foundation of the shower boost and of the current status of the development of an operational calorimeter prototype are presented. This concept could prove pivotal for both accelerator fixed-target experiments and satellite-borne ω-ray observatories.